Vantagens e desvantagens da aplicação da análise referencial das demonstrações contábeis como ferramenta de análise econômica, financeira e patrimonial - Reinaldo, Cristiano Melo (2007)
The companies, independently of his/her load, branch or market they can be used of several methodologies of acting of its activities , be through the operational analysis, or for the economical-financial analysis of the accounting demonstrations. It is known still that the results presented in the accounting demonstrations, they be used by the manager as tendency indicators in the projections of the accounting demonstrations of the future exercises. In that context of the analysis of the accounting demonstrations, this work presents the following question: Which the advantages and disadvantages of the reference with analysis of the accounting demonstrations what has how presupposition a single accounting base (certain value) in the evaluation of the results economical, financial and patrimonial of the companies, done use together with other techniques? The general objective is to present the advantages and disadvantages of the retrospective with analysis of the accounting demonstrations starting from a single accounting base and the specific objectives are: to present the characteristics of the accounting demonstrations and the importance of his/her analysis, through the traditional indicators economical-financial of the companies; to characterize the reference with analysis as one in the ways of analysis of the accounting demonstrations, and to to evaluate the application the reference with analysis, together with other techniques in the analysis of accounting demonstrations of the company Grendene S/A the methodology adopted in the research is classified as exploratory and of qualitative nature, being used of the bibliographical and documental methods to reach the proposed objectives. Finally, it is ended that the model of the reference with analysis of the accounting demonstrations can be used traditionally in combination with other types of analyses used by the manager and/or analysts of any organization, because the same allows to their users a differentiated retrospective vision of the obtaining and application of resources.